2006
DOI: 10.1902/jop.2006.050194
|View full text |Cite
|
Sign up to set email alerts
|

Local Gingival Blood Flow at Healthy and Inflamed Sites Measured by Laser Doppler Flowmetry

Abstract: LDFRs are positively correlated with the degree of gingival inflammation. GBF demonstrated significant differences in EG and CG. Modifications of the probe are needed to enhance its clinical applicability in clinical research of periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 49 publications
2
28
1
2
Order By: Relevance
“…However, in the same species, Baab and Öberg (2) found no significant correlation between the gingival index, GCF and blood flow and the elimination of the inflammation did not result in a decrease in blood flow either. In humans, experimentally induced gingivitis resulted in decreased blood flow to the gingiva (11,33) whereas developed gingivitis resulted in increased blood flow (11). GBF at rest was found to be smaller in periodontitis patients compared to the reference subjects (34) and the treatment of gingivitis (58) or periodontitis (15) reduced blood flow.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in the same species, Baab and Öberg (2) found no significant correlation between the gingival index, GCF and blood flow and the elimination of the inflammation did not result in a decrease in blood flow either. In humans, experimentally induced gingivitis resulted in decreased blood flow to the gingiva (11,33) whereas developed gingivitis resulted in increased blood flow (11). GBF at rest was found to be smaller in periodontitis patients compared to the reference subjects (34) and the treatment of gingivitis (58) or periodontitis (15) reduced blood flow.…”
Section: Discussionmentioning
confidence: 97%
“…One possible explanation for conflicting results is variations in gingival blood flow as a function of time and the location of the laser Doppler probe. Temporal variation related to biological variation may be influenced by many physiological factors in addition to the inflammation, such as circadian rhythm (54), blood pressure (50), temperature (20) or tooth brushing (11,45,55). Furthermore, although no data are available about the effects of disinfectant mouth rinses, eating and drinking on GBF they may also influence the recordings.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that laser Doppler flow readings (LDFRs) are positively correlated with the degree of gingival inflammation. LDFRs values were significantly higher in patients with experimental gingivitis than in healthy subjects [40]. Krishnan and coworkers also reported that orthodontic appliances can evoke local soft-tissue responses in many ways [41].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 When an infrared laser is exposed to red blood cells in microvessels, reflection and scattering occur, and Doppler shift causes a frequency change between the incidence and reflection in proportion to blood flow. This method has been introduced in dentistry, revealing the relationship between periodontal disease and blood flow in gingival, 8 blood flow recovery process analysis in periodontal surgery, 9,10 and the relationship between smoking and gingival blood flow. 11,12 It has also been applied to orthopedics to evaluate blood flow in joints, [13][14][15] to evaluate the effect of postoperative joint surgery, 16 and to diagnose rheumatoid arthritis.…”
mentioning
confidence: 99%